Following the leader : international order, alliance strategies, and emulation - Kuo, Raymond C. (Raymond Cheng) (Stanford scholarship online., 2021)
"Nations have powerful reasons to get their military alliances right. When security pacts go well, they underpin regional and global order; when they go wrong, they can spread wars across continents as states are dragged into conflict. We would, therefore, expect states to carefully tailor their military partnerships to specific conditions. This expectation, Raymond C. Kuo argues, is wrong. Following the Leader argues that most countries ignore their individual security interests in military pacts, instead converging on a single, dominant alliance strategy. The book introduces a new social theory of strategic diffusion and emulation, using case studies and advanced statistical analysis of alliances from 1815 to 2003. In the wake of each major war that shatters the international system, a new hegemon creates a core military partnership to target its greatest enemy. Secondary and peripheral countries rush to emulate this alliance, illustrating their credibility and prestige by mimicking the dominant form. Be it the NATO model that seems so commonsense today, or the realpolitik that reigned in Europe of the late nineteenth century, a lone alliance strategy has defined broad swaths of diplomatic history. It is not states' own security interests driving this phenomenon, Kuo shows, but their jockeying for status in a world periodically remade by great powers"-- Provided by publisher